SOS in a pandemic: Staffing strategies for COVID-19. Issue 4 (April 2021) - Moorer, Amanda; Klatt, Elizabeth; Thornton, Olivia; Groves, Thu-Nhi; Eisenach, Bree; Soholt, Kate; Haylett, Wendy J.; Hessler, Karen L.; Zwink, Jennifer
Abstract : In spring 2020, a large healthcare system spanning various state regions admitted over one-third of the state's COVID-positive patients. Learn how they developed an operational framework to effectively use all system RNs to address the ever-changing dynamic of frontline staffing.